Performance management - Aguinis, Herman (Pearson Prentice Hall, 2009)
"This text addresses the topic of performance management, a continuous process of identifying, measuring and developing the performance of individuals and teams and aligning performance with the strategic goals of the organization. Performance management systems are described as key tools to transform people's talent and motivation into a strategic organizational advantage. Topics include the design